London 2012 performance debrief (2012)
I. Following a lower than expected medal total at the London 2012 Olympic Games, British Swimming undertook a comprehensive Performance Debrief exercise. This was led by a panel of internal and external representatives, took place through September and October 2012 and followed an agreed six phased methodology comprising statistical analysis and range of iterative consultation activities with more than 80 stakeholders including athletes who competed at the Games.